Répartition de la biodiversité en France métropolitaine : une synthèse des Atlas faunistiques - Isabelle Witté; Julien Touroult (VertigO)
Atlases are regarded as a source of data of good quality regarding the presence of species in regular geographic grids. These data are commonly used to describe the distribution of individual species in France, but were rarely assembled in a multi-taxa study to reflect biodiversity as a whole. This paper is intended as a first step towards the valuation of data from faunal atlases on French territory. In this study, seven published atlases covering 507 vertebrate species and 425 insect species were combined for analyses. Different indices designed to pinpoint biodiversity hotspots were calculated for each quadrat in a regular grid covering the whole country : species richness, rare species richness, relative rarity index and an index of contribution to the global biodiversity calculated with spatial optimisation software (Marxan). Large scale zoogeographical ensembles were defined using ordination and classification methods. Seventeen synthetic maps are provided to illustrate the large-scale patterns of French biodiversity. This work is mostly intended as a descriptive approach ; therefore, only a limited ecological interpretation is provided. The relevance of the different indices, taxonomic representativeness and possible uses of these maps of biodiversity for conservation and public information are discussed.